2023
DOI: 10.1038/s41598-023-48084-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike receptor-binding domain is internalized and promotes protein ISGylation in human induced pluripotent stem cell-derived cardiomyocytes

Shota Okuno,
Shuichiro Higo,
Takumi Kondo
et al.

Abstract: Although an increased risk of myocarditis has been observed after vaccination with mRNA encoding severe acute respiratory syndrome coronavirus 2 spike protein, its underlying mechanism has not been elucidated. This study investigated the direct effects of spike receptor-binding domain (S-RBD) on human cardiomyocytes differentiated from induced pluripotent stem cells (iPSC-CMs). Immunostaining experiments using ACE2 wild-type (WT) and knockout (KO) iPSC-CMs treated with purified S-RBD demonstrated that S-RBD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…24 Multiple studies have shown an increased risk of myocarditis after vaccination with mRNA encoding SARS-CoV-2 spike protein. [25][26][27] mRNA vaccines can result in spike protein expression in muscle tissue, the lymphatic system, cardiomyocytes and other cells after entry into the circulation. 28 Recipients of two or more injections of the mRNA vaccines display a class switch to IgG4 antibodies.…”
mentioning
confidence: 99%
“…24 Multiple studies have shown an increased risk of myocarditis after vaccination with mRNA encoding SARS-CoV-2 spike protein. [25][26][27] mRNA vaccines can result in spike protein expression in muscle tissue, the lymphatic system, cardiomyocytes and other cells after entry into the circulation. 28 Recipients of two or more injections of the mRNA vaccines display a class switch to IgG4 antibodies.…”
mentioning
confidence: 99%